2018
DOI: 10.1111/jcmm.13572
|View full text |Cite
|
Sign up to set email alerts
|

Qiliqiangxin attenuates hypoxia‐induced injury in primary rat cardiac microvascular endothelial cells via promoting HIF‐1α‐dependent glycolysis

Abstract: Protection of cardiac microvascular endothelial cells (CMECs) against hypoxia injury is an important therapeutic strategy for treating ischaemic cardiovascular disease. In this study, we investigated the effects of qiliqiangxin (QL) on primary rat CMECs exposed to hypoxia and the underlying mechanisms. Rat CMECs were successfully isolated and passaged to the second generation. CMECs that were pre‐treated with QL (0.5 mg/mL) and/or HIF‐1α siRNA were cultured in a three‐gas hypoxic incubator chamber (5% CO2, 1% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 47 publications
0
31
0
Order By: Relevance
“…It has exhibited remarkable curative effect in clinical applications and holds the traditional functions of strengthening heart, diuresis and vasodilation [17,19,20,24]. Basic research shows that QLQX could restrain hypoxia-induced injury in primary rat cardiac microvascular endothelial cells via promoting glycolysis in a HIF-1a-dependent manner [27]. During hypoxia, cardiac microvascular endothelial cells (CMVECs) promote the expression of vascular endothelial growth factor (VEGF) and QLQX could attenuate this injury via facilitating hypoxia inducible factor-1α(HIF-1α)dependent glycolysis [28].…”
Section: Discussionmentioning
confidence: 99%
“…It has exhibited remarkable curative effect in clinical applications and holds the traditional functions of strengthening heart, diuresis and vasodilation [17,19,20,24]. Basic research shows that QLQX could restrain hypoxia-induced injury in primary rat cardiac microvascular endothelial cells via promoting glycolysis in a HIF-1a-dependent manner [27]. During hypoxia, cardiac microvascular endothelial cells (CMVECs) promote the expression of vascular endothelial growth factor (VEGF) and QLQX could attenuate this injury via facilitating hypoxia inducible factor-1α(HIF-1α)dependent glycolysis [28].…”
Section: Discussionmentioning
confidence: 99%
“…QLQX has been proven to have a great potential as a promising metabolic modulator as it can regulate cardiac glucose and FA metabolism simultaneously by upregulating a large number of enzymes, including GLUT4, GLUT1, CD36, and so forth in different pathological models (Shen et al, 2017;Wang et al, 2017Wang et al, , 2018. This multi-targeting regulation might depend on the multiple components identified in QLQX, encompassing ginsenoside Rb1, astragaloside, salvianolic acid A, and so forth (Zhang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Pyruvate dehydrogenase 1 (PDK1) is an essential enzyme for pyruvate dehydrogenation by the mitochondria [49]. In addition, several enzymes involved in glycolysis were found to be elevated, such as pyruvate kinase 2 (PK2), phosphofructokinase 1 (PFK1) and hexokinase 2 (HK2), in disease [50]. In our study, we also demonstrated that dexmedetomidine markedly decreased NADPHase, HK2, PFK1, PK2, Glut1, LDHA and PDK1 expression, which were induced by H 2 O 2, in rat DRG neurons.…”
Section: Discussionmentioning
confidence: 99%